2017
DOI: 10.1039/c6sc03993f
|View full text |Cite
|
Sign up to set email alerts
|

Complementary oligonucleotides regulate induced fit ligand binding in duplexed aptamers

Abstract: Hybridizing a complementary oligonucleotide to an ATP aptamer is shown to functionally regulate a newly revealed induced fit ligand-binding pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 54 publications
(40 reference statements)
3
43
0
Order By: Relevance
“…Representative ACE-Scan relative fluorescence values for F Hyb and F BufferOnly are plotted, and a representative dilution curve for 8 ligand concentrations is shown in cyan, with two fluorescence signals labeled ( F 1 µM , F 10 mM ). Importantly, DA dissociation rates in ACE-Scan are a sum of k off and k * off[Ligand] rates, and k * off[Ligand] is therefore calculated based on the increased dissociation rate, relative to k off , induced by the presence of ligand 15 . d Representative ACE-Scan images for three in vitro-selected aptamers (ATP DNA, ATP RNA, and thrombin DNA aptamers).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Representative ACE-Scan relative fluorescence values for F Hyb and F BufferOnly are plotted, and a representative dilution curve for 8 ligand concentrations is shown in cyan, with two fluorescence signals labeled ( F 1 µM , F 10 mM ). Importantly, DA dissociation rates in ACE-Scan are a sum of k off and k * off[Ligand] rates, and k * off[Ligand] is therefore calculated based on the increased dissociation rate, relative to k off , induced by the presence of ligand 15 . d Representative ACE-Scan images for three in vitro-selected aptamers (ATP DNA, ATP RNA, and thrombin DNA aptamers).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this prevailing model of DA-ligand-binding stands in contrast with the modeling of native aptamers, many of which are known to bind their ligand via induced fit 14 . Furthermore, we recently discovered that some ACEs give rise to, and regulate, induced fit ligand-binding in a small set of DAs engineered from an ATP DNA aptamer, with binding affinities one million-fold higher than predicted by conformational selection 15 . However, DA-to-ligand binding remains underexplored, and it is not yet understood whether ACE-regulated induced fit is an exception specific to the ATP DNA aptamer and subset of ACEs tested 15 , or if induced fit also arises in (i) ATP DNA DAs using other ACEs, or in (ii) DA families engineered from other DNA and RNA aptamers.…”
Section: Introductionmentioning
confidence: 99%
“…57 The binding-related conformational changes that occur, can be exploited for sensor applications involving fluorescent, electrochemical, colorimetric, and various other reporting mechanisms. 117,118 With this in mind it was important to further characterize switching abilities of the candidate's and to screen them for future applications.…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%
“…73 It has been suggested that the observed affinity of a duplexed aptamer is both a function of the intrinsic affinity of the native aptamer and the hybridization free energy of the aptamer capture probe duplex. 118 Modification to length location of antisense CPs as well as their length have been shown to affect observed affinity, and the performance hybridized biosensors. 141,142 Porshetta et al effectively tuned the relative affinity of cocaine hybridized signalling aptamers by over three orders of magnitude.…”
Section: Fluorescent Hybridized Probesmentioning
confidence: 99%
See 1 more Smart Citation